The complete chloroplast genome sequence of the medicinal plant Morinda officinalis (Rubiaceae), an endemic to China. (1st November 2016) - Zhang, Runjing; Li, Qian; Gao, Junli; Qu, Minhong; Ding, Ping
Abstract: The complete chloroplast genome of Morinda officinalis, an endangered and important Chinese medicine with great economic value, has been sequenced in this article. The genome size is 153 398 bp in length, with 38.05% GC content. A pair of inverted repeats (IRs, 51 834 bp) are separated by a large single copy region (LSC, 83 996 bp) and a small single copy region (SSC, 17 566 bp). The chloroplast genome contains 103 unique genes, 80 protein-coding genes, 19 tRNA genes, and 4 rRNA genes. In these genes, 8 genes contained 1 intron, and 2 genes comprised of 2 introns.